Посвятительное граффито из Нимфея [Anna Namoylik: A Dedicatory Graffito from Nymphaeum] - Намойлик, А. С. (Hyperboreus, 2009)
This article represents a graffito found during the excavations of the Bosporan city of Nymphaeum in 1984. It is incised on the wall fragment of hellenistic black-glazed kantharos of baggy type with amphora-shaped ornament made in technique of carving and dilute clay painting. The graffito consists of two lines situated one above the other: [...]ΜΑΧΟΣΒ / [...]ΗΠΙΩΙ. The beginnings of both lines are lost. Space after iota in the lower line exceeds average intervals between letters of the inscription, so the ending of this line has been completely preserved. Beta is likely to be the last letter of the upper line, though it is impossible to make sure of this. The palaeography of the inscription, shape and figuration of the vessel as well as archaeological context of the find suggest a date of the second half of the 3rd century BC. Nominative case of the first word and dative case of the second one indicate the dedication purpose of the inscription. The word in the first line seems to be the name of dedicator. The word in the second line is presumably a name of a God to whom the graffito was devoted. The ending [...]ΗΠΙΩΙ enables us to restore the name of Asclepios in dative case: Ἀσκλ]ηπιῶι. Beta, if being the last letter of the first line, can be interpreted as a figure (β = 2). Inscriptions containing names of dedicators and gods as well as quantity of liquid or amount of money brought to sanctuaries are known in Greece and its colonies. Beta probably signified two kotylai of the liquid that the kantharos stored, for example, olive oil or wine. If there still were any letters after beta, it is likely to be the first letter of the patronymic. Thus we interpret the graffito as [...]μαχος β’ [Ἀσκλ]ηπιῶι – (so-and-so) dedicated to Asclepios 2 (kotylai of oil) or [...]μαχος e. g. Βοσπορίχου / [Ἀσκλ]ηπιῶι – (so-and-so) son of e. g. Bosporikhos dedicated to Asclepios (this kantharos). This graffito is considered to be the first and still the only evidence of Asclepios being worshipped in Nymphaeum. It is one of the rare evidences of his cult all over the Bosporos.